Radiography essentials for limited practice - Long, Bruce W. (Elsevier Saunders, 2013)
Covers various content areas mandated by the American Society of Radiologic Technologists curriculum, including x-ray technology and techniques, anatomy, pathology and positioning, radiation safety, patient care, and other clinical skills you may be required to perform.